Giant condyloma acuminata: Incidence among cases diagnosed as carcinoma of the penis - Davies, Sylvia W. (1965)
Twenty-four cases of giant condyloma acuminata were found among 100 cases diagnosed as carcinoma of the penis. One of the 24 tumours showed early malignant change. The characteristic histological pattern of giant condyloma consists of broad processes composed of prickle cells associated with little keratinization. The malignant condylomas show, in comparison, a loss of prickle cell preponderance, increased basal cell activity and frequent keratinization, or may present as a solid papillary epithelioma forming broad sheets of uniform cells with many mitoses. The incidence of malignant change in the giant condyloma and the relationship between the benign and malignant tumours are discussed.